2011
DOI: 10.3109/02713683.2011.618289
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association with PEDF Met72Thr Variant in Neovascular Age-related Macular Degeneration and Polypoidal Choroidal Vasculopathy in a Han Chinese Population

Abstract: No evidence was found to support a role for the Met72Thr variant in susceptibility to either PCV or nAMD in a Han Chinese cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…However, one GWA study did not provide genotype or allele data in controls and was excluded from further analysis 52 . Therefore, a total of 8 case-control studies were finally included for the meta-analysis 40 41 42 43 44 45 46 53 , involving 2284 AMD cases versus 3416 controls, and 317 PCV cases versus 371 controls. The main characteristics of the included studies were summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, one GWA study did not provide genotype or allele data in controls and was excluded from further analysis 52 . Therefore, a total of 8 case-control studies were finally included for the meta-analysis 40 41 42 43 44 45 46 53 , involving 2284 AMD cases versus 3416 controls, and 317 PCV cases versus 371 controls. The main characteristics of the included studies were summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Risk of population stratification presented in 1 study, which used spouses and friends as control subjects 53 . There was risk of confounding bias in 5 studies, in which results were not adjusted for confounding variables 40 41 45 46 53 . All the studies reported Hardy-Weinberg equilibrium (HWE) in controls.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations